1996
DOI: 10.1042/bj3160175
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-stimulating hormone rapidly stimulates inositol polyphosphate formation in FRTL-5 thyrocytes without activating phosphoinositidase C

Abstract: The thyroid-stimulating hormone (TSH) receptor is widely regarded as one of a limited number of G-protein-coupled receptors that activate both adenylate cyclase and phosphoinositidase C (PIC) via G-proteins, but the existing experimental evidence for TSH-stimulated PtdIns(4,5)P2 hydrolysis remains inconclusive. We have compared the effects of TSH and of ATP (acting via P2-purinergic receptors) on the inositol lipids and polyphosphates of [2-3H]inositol-labelled FRTL-5 rat thyroid cells. ATP initiated a rapid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…While many studies have concluded or assumed that the effects of TSH on inositol phosphate turnover and calcium are the result of activation of phospholipase C, the kinetics of TSH-induced changes in membrane inositol phosphates do not correspond to those of a classical phospholipase C agonist (Singh et al 1996). Indeed, data from this laboratory show that, under conditions in which lithium significantly inhibited TSH-stimulated cAMP accumulation in cultured pig cells, there was no hydrolysis of phosphatidylinositol or accumulation of diacylglycerol .…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…While many studies have concluded or assumed that the effects of TSH on inositol phosphate turnover and calcium are the result of activation of phospholipase C, the kinetics of TSH-induced changes in membrane inositol phosphates do not correspond to those of a classical phospholipase C agonist (Singh et al 1996). Indeed, data from this laboratory show that, under conditions in which lithium significantly inhibited TSH-stimulated cAMP accumulation in cultured pig cells, there was no hydrolysis of phosphatidylinositol or accumulation of diacylglycerol .…”
Section: Discussionmentioning
confidence: 66%
“…Possibly, the accumulating cAMP was exerting some crosstalk, which ultimately led to an elevation in intracellular calcium concentration. This possibility has previously been explored by ourselves and other workers using forskolin to increase cAMP (Ye et al 1991, Singh et al 1996. Both studies concluded that forskolin was unable to mimic the actions of TSH on intracellular calcium (Ye et al 1991) or inositol phosphate turnover (Singh et al 1996).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations